ABU ABDULLAH MUHAMMAD IBN ISMAIL AL-BUKHARI IS A GREAT MUHADDITH AND THE FOUNDER OF ENLIGHTENMENT - Samiyev Asroridin Sayfidinovich (Scholar Express Journal, 2023)
In this article, "Amir ul-mo'minin" "Imam al-muhaddisiyn", who was born and raised in the land of Uzbekistan and who made an unparalleled contribution to the development of world science, who surprised the scientists of the world with his knowledge, intelligence, and strong unique memory, in the Islamic world "Leader of all Muhaddiths", he thought about the life activity, scientific heritage and contribution to the development of world science of our compatriot Imam al-Bukhari, and the use of these sources of scientific, educational and spiritual-ethical education in the education of the current generation it is stated that it is one of the urgent problems of the day.
Keywords: Science; scientific heritage; muhaddis